PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID MATERI SEJARAH PERGERAKAN SMA DI LAMPUNG - Heru Puspo Aji Gumelar; Bobi Hidayat; Kuswono Kuswono (Swarnadwipa, 2019)
The purpose of this development is to develop an Android-based intractive learning media using iSpring Suite 8 which is feasible and practical when used. The method used in this research is 4-D which consists of the define stage, the design stage, the development stage and the dissemination stage. The datacollection instrument was in the form of a questionnaire, consisting of an expert validation questionnaire and a student response questionnaire. Data analysis techniques used in this study included several steps, namely data analysis, data tabulation, and interpreting the percentage of the questionnaire. The validationresults obtained from the development of the developed learning media are stated to be very feasible with a percentage. The validation of media experts got 86% results and material expert validations got 84% results, and the average was 85%. The results of the small group trial were stated to be practical with a result of 80%. Based on the predetermined criteria, the development of androd-based intractive learning media is declared feasible and practical.Keywords: instructional media, interactive media, history of movement in Lampung.